Microalgae From Physiology to Application - Vítová, Milada (IntechOpen, 2020)
The term microalgae is often used in the algal research community to collectively describe microscopic algae and cyanobacteria. Research of microalgae has expanded enormously, namely because of their significant commercial potential. The thorough knowledge of the physiology of microalgae must precede any commercial exploitation. We have to understand the mechanisms underlying the physiological and biochemical processes in the algal cells. The book Microalgae - From Physiology to Application covers major aspects of microalgae physiology and the possible applications in the sphere of biotechnology. This book gives a comprehensive overview of what is known about microalgae growth and production, secondary metabolites, and development of new species and products for commercialization. This volume should allow readers at all levels an entry into the exciting world of algal research.